DNER modulates adipogenesis of human adipose tissue‐derived mesenchymal stem cells via regulation of cell proliferation - Park, J.‐R. (Cell Prolif, 2009)
Objectives:  In recent years, obesity has become a global epidemic, highlighting the necessity for basic research into mechanisms underlying growth of adipose tissue and differentiation of stem cells into adipocytes, in humans. For better understanding of cell signalling in adipogenesis, the role of DNER (delta/Notch‐like EGF‐related receptor) in adipogenic differentiation of human adipose tissue‐derived mesenchymal stem cells (hAMSC) was investigated. Materials and methods:  To assess the role of DNER in hAMSC adipogenesis, hAMSCs were transfected with DNER small interfering RNA (siDNER). Real‐time quantitative reverse transcriptase polymerase chain reactions to assess expression levels of adipogenesis‐related genes regulated by siDNER, cell cycle and immunoblot analyses were performed. Results:  First, it was determined that DNER mRNA was profoundly expressed in hAMSCs and reduced during adipogenic differentiation. Knockdown of DNER altered cell morphology, inhibited proliferation and increased frequency and efficiency of adipogenesis in hAMSC. Expression of CCAAT/enhancer‐binding protein δ increased and proportion of cells in S phase decreased by knockdown of DNER, using specific siRNA. Moreover, adipocyte‐specific genes including peroxisome proliferator‐activated receptor gamma, fatty acid binding protein 4 and perilipin were up‐regulated in siDNER compared to the siControl group during adipogenesis in hAMSC. Conclusions:  These results indicate that DNER knockdown in hAMSC accelerated onset of adipogenic differentiation by bypassing mitotic clonal expansion during the early stages of adipogenesis.